Short and long-term survival following an in-hospital cardiac arrest in a regional hospital cohort. (October 2019) - Doherty, Zakary; Fletcher, Jason; Fuzzard, Kim; Kippen, Rebecca; Knott, Cameron; O'Sullivan, Belinda
Abstract: Introduction: Evidence about the immediate survival from in-hospital cardiac arrest (IHCA) is well established, however, beyond discharge there is very little describing the long-term outcomes of these patients. Of the few existing studies, all have been conducted in metropolitan centres. Therefore, this study describes survival from IHCA in both the short and long-term in a large regional hospital cohort. Method: A retrospective cohort study was conducted including all adult patients who suffered an IHCA between 1 February 2000 and 31 December 2017 in a large regional (non-metropolitan) hospital in Victoria, Australia. Characteristics of the arrest and patient were sourced from a prospectively collected database that captures all of the arrests occurring in the hospital. Mortality data after discharge were sourced from the state death registry, censored on 31 January 2018. Results: A total of 629 patients were included in the study. Of these, 357 (57%) survived the event, and 213 (34%) survived to discharge. At one-year post-arrest 27% of the original cohort were still alive. The age of the patient, arrest rhythm, location and duration of resuscitation were all significantly associated with long-term survival. Conclusion: Both short and long-term survival following an IHCA in a regional hospital are similar to previously described rates in metropolitan hospitals. Further research is required on the post-discharge correlates of long-term survival.